POSSIBILITY OF COMPUTER EXPERIMENT IN STUDY OF ANIMAL SPERMATOZOA HETEROGENEITY L. V. Gorbunov, Y. M. Mazharova - L. V.; Y. M. (Biotechnologia Acta, 2016)
A simulation model for evaluating the survival and fertilizing capacity of animal spermatozoa was developed, taking into account the initial condition of the sperm and the effectiveness of cryopreservation stages. The model is based on an analytical expression that reflects the main reasons for the survival of reproductive cells in onto-, techno- and phylogenesis. The decrease in spermatozoa resistance depends on a number of biological factors — the animal species, physiological conditions of sperm donor and recipient, the ejaculate quality, and technological factors — the effectiveness of the methods of cell cryopreservation and egg insemination. The discrepancy between the results of cell motility obtained by calculation and experimental methods amounted to less than 2% as a result of our own experiments and to less than 5% for the data taken from literature. A feature of the model is the complete independence of the effectiveness of studied techniques from the heterogeneity of animal sperm.